National cancer control plans: a global analysis. Issue 10 (October 2018) - Romero, Yannick; Trapani, Dario; Johnson, Sonali; Tittenbrun, Zuzanna; Given, Leslie; Hohman, Karin; Stevens, Lisa; Torode, Julie S; Boniol, Mathieu; Ilbawi, André M
Summary: There is increasing global recognition that national cancer plans are crucial to effectively address the cancer burden and to prioritise and coordinate programmes. We did a global analysis of available national cancer-related health plans using a standardised assessment questionnaire to assess their inclusion of elements that characterise an effective cancer plan and, thereby, improve understanding of the strengths and limitations of existing plans. The results show progress in the development of cancer plans, as well as in the inclusion of stakeholders in plan development, but little evidence of their implementation. Areas of continued unmet need include setting of realistic priorities, specification of programmes for cancer management, allocation of appropriate budgets, monitoring and evaluation of plan implementation, promotion of research, and strengthening of information systems. We found that countries with a non-communicable disease (NCD) plan but no national cancer control plan (NCCP) were less likely than countries with an NCCP and NCP plan or an NCCP only to have comprehensive, coherent, or consistent plans. As countries move towards universal health coverage, greater emphasis is needed on developing NCCPs that are evidence based, financed, and implemented to ensure translation into action.